Preface - Pareek, Chandra Shekhar (Translational Research in Veterinary Science, 2021)
Third volume and the second issue (Year 2020) of the scholarly open-access journal Translational Research in Veterinary Science (TRVS), Nicolaus Copernicus University (NCU) publishers is publishing four research papers devoted in the field of veterinary science. In this published issue of TRVS, three manuscripts based on the original research works and a case report. The first paper of Czarnik et al. (2020) published the original research paper based on the trait-associated study conducted on Polish HF cattle to find out the genetic association between bovine CXCL8 gene polymorphism and clinical mastitis and fertility trait; the second paper of Kwiatkowska et al. (2020) published the case report study on cat suffering from gastrointestinal lymphoma to examine the association of toxic encephalopathy with low dose metronidazole therapy; the third paper of Yemets (2020) published the original research paper based on the animal nutrition studies describing the dietary effects of drone larves homogenate on the homeostatic constants and the reproductive capacity of Large White gilts in Ukraine; and lastly the Bak et al. (2020) published the original research paper based on the use of algorithms for multiple DNA sequence alignment across livestock species. During this difficult period of COVID-19 pandemic year, I would like to thank all authors for their contribution to this issue. Thanks are also extended to the editorial board members, manuscripts reviewers, TRVS editorial technical staff working at NCU publisher office (Mirosława Buczyńska, Elżbieta Kossarzecka, Grzegorz Kopcewicz, and Dariusz Żulewski), who supported at every stage of the project. Most importantly, this volume of TRVS is greatly acknowledged the supported of NCU funds from newly elect JM Rector Prof. dr hab. Andrzej Sokala.